Accounting principles 2 - Arganda, Amelia M.; Cardenas-Atis, Teresa ;Del Rosario, Bernardo G., Jr. (Mandaluyong City, Philippines : National Book Store, 2002)
The text is so designed in a procedural approach. The use of special journals and subsidiary ledgers are also discussed in detail.
1. Merchandising concern -- 2. Purchase of Merchandise and other assets -- 3. Sale of merchandise and other assets -- 4. Payment of accounts and expenses -- 5. Collection of receivables and other income -- 6. Special journals and subsidiary ledgers -- 7. Trial balance. 8-column worksheet -- 8. Adjusting entries and 12-column worksheet -- 9. Financial statements.
Keywords: ACCOUNTING